Agile Strategy: Output from AquaData Workshop - Chénier, Jean-François; Galvao Rocha, Aline; Longobardi, Lorenzo; Dam Lam, Rodolfo; Kristofikova, Nurvitria; Keck, Angus; Boulet, Tom; Tilley, Alexander; Rossignoli, Cristiano (WorldFish, 2022)
WorldFish and AgUnity conducted a workshop for the AquaData initiative from 15 November to 17 November 2022. This document outlines some of the key outputs from those three days and the minimum viable product that emerged as the leading candidate for initial development.